2021
DOI: 10.3389/fpsyg.2021.682824
|View full text |Cite
|
Sign up to set email alerts
|

State Anhedonia in Young Healthy Adults: Psychometric Properties of the German Dimensional Anhedonia Rating Scale (DARS) and Effects of the COVID-19 Pandemic

Abstract: Healthy reward processing is a complex interplay of several components. Recent self-report measures of anhedonia, the decrease or loss of hedonic capacity, take this complexity into account. The Dimensional Anhedonia Rating Scale (DARS) measures interest, motivation, effort and consummatory pleasure across four domains: hobbies, food/drink, social activities and sensory experiences. In the present cross-sectional survey study, we validated the German version of the DARS in a sample of 557 young healthy adults.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
10
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 82 publications
4
10
0
1
Order By: Relevance
“…For construct validity, the CFA indicated a good fit to the four‐factor structure model in typical Chinese adolescents and individuals with MDD and SD. In line with our findings, previous studies have also reported that the DARS has a robust four‐factor structure in adults with a different cultural background, such as Canadian, Spanish, German, and Chinese settings (Arrua‐Duarte et al, 2019; Jia et al, 2020;Rizvi et al, 2015; Wellan et al, 2021). This suggests that the four‐factor structure of the DARS is invariable and universal across different ages and cultural backgrounds.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For construct validity, the CFA indicated a good fit to the four‐factor structure model in typical Chinese adolescents and individuals with MDD and SD. In line with our findings, previous studies have also reported that the DARS has a robust four‐factor structure in adults with a different cultural background, such as Canadian, Spanish, German, and Chinese settings (Arrua‐Duarte et al, 2019; Jia et al, 2020;Rizvi et al, 2015; Wellan et al, 2021). This suggests that the four‐factor structure of the DARS is invariable and universal across different ages and cultural backgrounds.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, the DARS demonstrates good divergent validity, as its correlations with the BIS scores were small to none. The BIS scale has been linked to dysfunctional impulsive‐related behaviors, which is completely different from the construct of anhedonia (Rizvi et al, 2015; Wellan et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When the studies are examined in detail, it is seen that this process is often associated with two different concepts separately. These concepts are the concept of "alienation", which is one of the research areas of social psychology, and "social anhedonia", which is a neuropsychological concept [11][12][13][14].…”
Section: Original Articlementioning
confidence: 99%
“…Allerdings zeigen die Studien, dass die einzelnen PVS-Subkonstrukte im subjektiven Selbstbericht durch den Fragebogen nicht differenzierbar waren, in Übereinstimmung mit anderen Fragebogenstudien, etwa im Bereich der Anhedonie, die ebenfalls nur Belohnungstypen unterscheiden konnten (z. B. bei der DARS [ 31 , 44 ]). Was bedeutet das?…”
Section: Translationale Aspekte („Bench-to-bedside“) Der Rdoc-pvsunclassified